Automated invention for smart industries : 18th International TRIZ Future Conference, TFC 2018, Strasbourg, France, October 29-31, 2018, Proceedings /: 18th International TRIZ Future Conference, TFC 2018, Strasbourg, France, October 29-31, 2018, Proceedings. (2018) - Unknown
No abstract available